The Assignment of the Different Infrared Continuum Absorbance Changes Observed in the 3000–1800-cm(−1) Region during the Bacteriorhodopsin Photocycle - Garczarek, Florian (Biophysical Society, 2004)
The bleach continuum in the 1900–1800-cm(−1) region was reported during the photocycle of bacteriorhodopsin (bR) and was assigned to the dissociation of a polarizable proton chain during the proton release step. More recently, a broad band pass filter was used and additional infrared continua have been reported: a bleach at >2700 cm(−1), a bleach in the 2500–2150-cm(−1) region, and an absorptive behavior in the 2100–1800-cm(−1) region. To fully understand the importance of the hydrogen-bonded chains in the mechanism of the proton transport in bR, a detailed study is carried out here. Comparisons are made between the time-resolved Fourier transform infrared spectroscopy experiments on wild-type bR and its E204Q mutant (which has no early proton release), and between the changes in the continua observed in thermally or photothermally heated water (using visible light-absorbing dye) and those observed during the photocycle. The results strongly suggest that, except for the weak bleach in the 1900–1800-cm(−1) region and >2500 cm(−1), there are other infrared continua observed during the bR photocycle, which are inseparable from the changes in the absorption of the solvent water molecules that are photothermally excited via the nonradiative relaxation of the photoexcited retinal chromophore. A possible structure of the hydrogen-bonded system, giving rise to the observed bleach in the 1900–1800-cm(−1) region and the role of the polarizable proton in the proton transport is discussed.